A Comparison of Traditional and Modern Qur’anic Teaching Methods in Islamic Education - Aini, Siti Noor (Journal of Noesantara Islamic Studies, 2025)
The evolving landscape of Islamic education necessitates an examination of traditional and modern Qur’anic teaching methods to address the demands of contemporary learners. Traditional methods, such as rote memorization (tahfiz) and teacher-centered approaches, have been central to Qur’anic education for centuries. In contrast, modern methods emphasize interactive and learner-centered pedagogies, incorporating technology and critical thinking. This study compares these approaches to evaluate their effectiveness in fostering Qur’anic understanding and engagement among students. The research aims to identify the strengths and limitations of both teaching methods, providing insights into their impact on students’ comprehension, retention, and spiritual connection with the Qur’an. A mixed-methods approach was employed, combining surveys and interviews with students, teachers, and education experts across Islamic schools and institutions. Comparative analysis of classroom observations further enriched the findings. The results reveal that traditional methods excel in promoting memorization and discipline but often lack adaptability to diverse learning needs. Modern methods, while fostering critical thinking and engagement, face challenges in maintaining traditional values and spiritual depth. The study concludes that an integrative approach, combining the strengths of both methods, offers the most effective strategy for Qur’anic education in the modern era.